Ratio of momentum diffusivity to thermal diffusivity : introduction, meta-analysis, and scrutinization /: introduction, meta-analysis, and scrutinization. (2022) - Animasaun, Isaac Lare; Shah, Nehad Ali; Wakif, Abderrahim; Mahanthesh, Basavarajappa; Sivaraj, Ramachandran; Koríko, Olubode Kolade
No abstract available